(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The editor’s editorial describes the contents of the special issue dedicated to environmental crime and remembers the sociologist Bianca Beccalli, a former lecturer at the Faculty of Political Science who passed away recently.